Experience of nursing students upon their first care encounter with terminally ill patients - Muñoz-Pinov, Irene Pamela (Investigación y Educación en Enfermería, 2014)
Objective. This work seeks to describe the experiences endured by third- and fourth-year nursing students upon their first care encounter with a terminally ill patient. Methodology. This was a descriptive qualitative study with methodology of analysis of contents of written testimonies at the end of the care experience. The study had the participation of 65 students from a private university in Santiago, Chile. Results. Emerging themes were classified into seven categories: life learning is accomplished, feelings regarding the encounter, loving care, interdisciplinary work with comprehensive care, sense to nursing, incorporation of the family in caring, and development of communication skills. Conclusion. The experiences of the nursing students show they have difficulties in facing the care of an individual in process of death. Educational strategies should be posed to improve undergraduate formation on end-of-life care.